CORRELATION OF NUTRITIONAL STATUS OF MOTHER AND THE BIRTH WEIGHT OF THE BABY - Salunkhe, Avinash H; Pratinidhi, Asha; Sv, Kakade; Salunkhe, Jyoti A; Mohite, Vaishali R; Bhosale, Trupti (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to correlate mother's nutritional status during pregnancy and determine the birth weight of the baby. Methods: A comparative, exploratory approach and prospective cohort study design was used to find out mothers' nutritional status during pregnancy influences the birth weight of babies. The data were collected using structured interview schedule and dietary history by 24 h recall method from a randomly selected sample of 380 eligible mothers delivered at Krishna Hospital, Karad. Results: There was a significant correlation between birth weight and calorie intake (correlation coefficient [r]=0.595; p<0.001; Chi-square=201.3; p<0.001.) A higher proportion of low birth weight babies, i.e., 105 (32.2%) were delivered by the mothers consuming <70% of protein ([r]=0.245; p<0.001; Ï‡2=24.033; p<0.001]). There was correlation between birth weight and calcium intake of mothers ([r]=0.525; p<0.001; Ï‡2=10.12; p<0.001] birthâ€ weight and iron intake of mothers ([r]=0.250; p<0.001; Ï‡2=13.798; p<0.001). Conclusion: The intake of calorie, protein, calcium, and iron of mother can significantly influence the weight of the newborn baby. Among all anthropometric parameters of the mother, weight gain was the strongest predictor of adequacy of the birth weight.